2021
DOI: 10.1021/acsomega.1c00021
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Urea Deposit Formation Process in a Selective Catalytic Reduction System of a Diesel Engine Based on a Fluid–Solid Coupling Method

Abstract: Currently, selective catalytic reduction (SCR) systems have become an essential part in diesel engines, and urea crystallization is one of the most serious issues in SCR systems. In this paper, the urea deposit formation processes in the SCR system were investigated by numerical simulations based on a fluid−solid coupling method. The results show that the masses of the wall film and solid urea are larger at conditions with lower temperatures and higher injection rates. At higher temperatures, cyanate ions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…29 ms ASOI, compared to 10 ms ASOI for the conventional injection. The distribution of the temperature corresponded to the locations of the droplet-wall collisions and wetting regions, as well as to the liquid film deposition, which is consistent with the analysis of Li et al [19]. Consequently, the application of the flash-boiling injection resulted in a total reduction of the liquid film in low-mass flowlowmass-flow rate rated conditions and a substantial reduction for the higher mass flow rate (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…29 ms ASOI, compared to 10 ms ASOI for the conventional injection. The distribution of the temperature corresponded to the locations of the droplet-wall collisions and wetting regions, as well as to the liquid film deposition, which is consistent with the analysis of Li et al [19]. Consequently, the application of the flash-boiling injection resulted in a total reduction of the liquid film in low-mass flowlowmass-flow rate rated conditions and a substantial reduction for the higher mass flow rate (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Application The application of a superheated spray along with an appropriate injection angle led to an increased uniformity of ammonia distribution and a significant reduction of liquid film, which minimises the risk of solid deposit development. The importance of the injector's location and its inclination in the aftertreatment system with regard to a solid deposit formation was pointed out by Li et al [19]. Those parameters were particularly meaningful in the cases of relatively low flow temperatures.…”
Section: Introductionmentioning
confidence: 98%
“… The ammonia-laden exhaust gas is then introduced into a monolithic reactor where NO X reduction is carried out in the presence of a vanadium catalyst impregnating the monolithic ceramic support via reactions –. ,, Urea decomposition at the inlet of the catalytic reactor is a bottleneck that must be maximized by proper design. Experimental and numerical studies on nozzle angle and atomization chamber length have been conducted to optimize the mixing of the exhaust gas and urea solution, as well as the rate of urea decomposition. Other SCR studies have focused on the chemistry and thermodynamics of urea decomposition, the mechanism of salt formation in the SCR catalyst chamber, the sedimentation rate of byproducts, and the sequential mixing chamber for urea decomposition . Other advances from SCR research and development concern the “mixerless urea-SCR” geometry, in which the conventional static mixer is replaced by a compact spherical chamber allowing high urea decomposition while preventing the formation of liquid films on the walls and at the inlet of the catalytic chamber .…”
Section: Exhaust Gas Cleaning Systems (Egcs)mentioning
confidence: 99%
“…Therefore, the careful design process of mixers is crucial for beneficial selective catalytic reduction. The liquid film and solid deposit formation process was numerically investigated by Li et al [30] for the perforated mixer. The authors observed that in the case of relatively high temperatures the mixer's geometry had a primary influence on the deposit's location; while at lower temperatures, its location was more dependent on the position and orientation of the UWS injector.…”
Section: Introductionmentioning
confidence: 99%